Recurrent parvovirus B19 viremia resulting in two episodes of hemophagocytic lymphohistiocytosis - Hans Martin Orth; Andre Fuchs; Nadine Lübke; Björn-Erik Ole Jensen; Tom Luedde (Virology Journal, 2022)
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory condition with uncontrolled activation of lymphocytes and macrophages. Besides a primary (genetic) form, HLH can also be triggered by malignant, autoimmune and infectious diseases. HLH recurrences are rarely described, usually only in primary HLH. Parvovirus B19 (PVB19) Infection is one of the rare and rather benign causes of HLH. Since the infection usually results in long-lasting immunity, recurrent viremia is very uncommon. Case presentation We report an unusual case of a young female with recurrent PVB19 infection that led to repeated episodes of HLH. The first episode occurred at the age of 25 years with a three-week history of high fever and nonspecific accompanying symptoms. The diagnosis of HLH was confirmed by HLH-2004 criteria and HScore, PVB19 viremia was detected as underlying cause. Following guideline-based therapy, the patient was symptom-free for one year, before similar symptoms recurred in a milder form. Again, PVB19 was detected and HLH was diagnosed according to HScore. After successful treatment and a nine-month symptom-free interval, a third phase of hyperinflammation with low PVB19 viremia occurred; this time, treatment with a corticosteroid and intravenous immunoglobulin was initiated before the presence of clear diagnostic criteria for HLH. No further events occurred in the following three years. Conclusions In the case of our patient, the recurrent viremia triggered three episodes of hyperinflammation, two of which were clearly diagnosed as HLH. To our knowledge, this is the first published case of recurrent HLH due to PVB19 infection. Therefore, the case gives new insights in triggering mechanisms for HLH.